Back Cover: Small‐Molecule APOBEC3G DNA Cytosine Deaminase Inhibitors Based on a 4‐Amino‐1, 2, 4‐triazole‐3‐thiol Scaffold (ChemMedChem 1/2013). Issue 1 (23rd December 2012) - Olson, Margaret E.; Li, Ming; Harris, Reuben S.; Harki, Daniel A.
<x xml:space="preserve">Abstract</x> The back cover picture shows that APOBEC3G (A3G)‐mediated cytosine deamination of single‐stranded DNA oligonucleotides can be inhibited by 4‐amino‐1, 2, 4‐triazole‐3‐thiol‐based small molecules. Engagement of A3G C321, which is proximal to the active site, confers activity for this class of compounds. For more details, see the Full Paper by Daniel A. Harki et al. on p. 112 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>